Estudo de estabilidade de frequência em sistemas elétricos de potência considerando turbinas hidráulicas - Guelbert, Ewerlyn Ane Perússolo (2015)
Electric energy shows itself necessary day by day of people. Currently we don’t have another way that is more convenient of holding up the technology provided by it. However the society stays vulnerable to certain problems that can occur if in the increase or decrease of energy requested to the Interconnected Brazilian System, the frequency doesn’t return to its nominal value (for Brazil the value is 60 Hz).Thus, this monograph approaches mainly the problem of Load-Frequency Control in electric power systems .For this study, it emphasizes the understanding the control of the mesh of secondary regulation, commonly called Automatic Generation Control (AGC), which has the main objective, the restoration of frequency to its original value. For the development of this knowledge a review was made of basic concepts of responsible controls for primary and secondary regulation, as well as the presentation of the theoretical study of mathematical modeling of machines and the presentation of the kinds of existing hydraulic turbines. At last this work ends with simulations of control blocks, using Simulink of MATLAB, in order to analyze responses time when applying an unit step signal (more critical situation of Electric Power System) according the system with a generic hydraulic turbine.